SIMULATION DEVELOPMENT ON UNREAL ENGINE AND THEIR APPLICATIONS IN EDUCATION PROCESS - Elksne, Mārīte; Solovjovs, Artūrs; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Due to the rapid development of technology in various fields of science, a new problem related to excessive resource consumption arises, as most of the experiments and demonstrations require a certain amount of materials and substances to be successfully performed. The aim of this work is to create a realistic simulation using Unreal Engine 4 and give an insight into its practical applications in education process. Authors have also gathered general information about simulation development and Unreal Engine 4 environment. As a result, a simulation showing friction of three different materials was created. It was also concluded that such applications could replace ordinary experiments because of their simple modifiability and minimal long-term resource consumption.